Trophic niche variation driven by water level fluctuations facilitates the co‐occurrence of invasive tilapia species in a subtropical reservoir in China - Lei Yang; Chuansong Liao; Xiang Ji; Xuemei Chen; Mingde Guo; Guilin Zhang; Mayara Pereira Neves; Yuanqing Wang; Hang Zhang; Chuanbo Guo; Jiashou Liu (Journal of Fish Biology, 2025)
Investigating how multiple invasive fish species with similar ecological traits respond to different environmental conditions is crucial to understanding their successful invasion and coexistence. Here, we used stomach content analysis and stable isotope analysis to analyse the effects of water level fluctuation on the trophic niche plasticity of three dominant co‐occurring invasive tilapia species ( Coptodon zillii , Sarotherodon galilaeus , and Oreochromis niloticus ) in the Shanmei Reservoir, southern China. We found that the tilapia species exhibited an iliophagous habit with dietary variations between the high‐water (HW) and low‐water (LW) level periods. During the LW period, tilapia fishes primarily fed on periphytic algae, whereas during the HW period, they reduced their consumption of epiphytic algae and increased their intake of plant remains. Biofilms were the most assimilated resource by the species during the LW period, whereas riparian plants dominated during the HW period. The niche width and niche overlap of the three tilapia species were significantly greater in the HW period than in the LW period. However, their trophic positions were not significantly affected by water level fluctuations. Our findings indicate that temporal variation in diet composition and trophic niche, driven by water level fluctuations, may favor food resource partitioning and facilitate the coexistence of these invasive tilapia species.